Option-Game Approach to Analyze Technology Innovation Investment under Fuzzy Environment - Yingshuang Tan; Yong Long (Journal of Applied Mathematics)
Based on the model of symmetric and asymmetric duopoly option game, this paper discusses the present value of profit flows and the sunk investment costs for the trapezoidal fuzzy number. It constructs the fuzzy expressions of the investment value and investment threshold of followers and leaders under fuzzy environment and conducts numerical analysis. This offers a kind of explanation to the investment strategies under fuzzy environment.